Alkaline Salts to Counteract Bone Resorption and Protein Wasting Induced by High Salt Intake: Results of a Randomized Controlled Trial - Buehlmeier, Judith; Frings-Meuthen, Petra; Remer, Thomas; Maser-Gluth, Christiane; Stehle, Peter; Biolo, Gianni; Heer, Martina (The journal of clinical endocrinology and metabolism, 2012)
High sodium chloride (NaCl) intake can induce low-grade metabolic acidosis (LGMA) and may thus influence bone and protein metabolism.We hypothesized that oral potassium bicarbonate (KHCO3) supplementation may compensate for NaCl-induced, LGMA-associated bone resorption and protein losses. Eight healthy male subjects participated in a randomized trial with a crossover design. Each of two study campaigns consisted of 5 d of dietary and environmental adaptation followed by 10 d of intervention and 1.5 d of recovery. In one study campaign, 90 mmol KHCO3/d were supplemented to counteract NaCl-induced LGMA, whereas the other campaign served as a control with only high NaCl intake.When KHCO3 was ingested during high NaCl intake, postprandial buffer capacity ([HCO3−]) increased (P = 0.002). Concomitantly, urinary excretion of free potentially bioactive glucocorticoids [urinary free cortisol (UFF) and urinary free cortisone (UFE)] was reduced by 14% [∑(UFF,UFE); P = 0.024]. Urinary excretion of calcium and bone resorption marker N-terminal telopeptide of type I collagen was reduced by 12 and 8%, respectively (calcium, P = 0.047; N-terminal bone collagen telopeptide, P = 0.044). There was a trend of declining net protein catabolism when high NaCl was combined with KHCO3 (P = 0.052).We conclude that during high salt intake, the KHCO3-induced postprandial shift to a more alkaline state reduces metabolic stress. This leads to decreased bone resorption and protein degradation, which in turn might initiate an anticatabolic state for the musculoskeletal system in the long run.